A new dwarf crayfish (Decapoda: Cambaridae) from floodplain swamps in central Alabama - Schuster, Guenter A.; Kendrick, Michael R. (Zootaxa, 2017)
Cambarellus (Pandicambarus) rotatus, new species, is a dwarf crayfish from floodplain swamps in the Tombigbee and Black Warrior river drainages of Greene, Hale, and Marengo counties, Alabama. The new species is morphologically most similar to Cambarellus (Pandicambarus) lesliei. They differ in a several morphological characters. Cambarellus rotatus, new species, has gonopods that are rotated mesially so that the terminal elements oppose each other, and they have a short C-shaped sperm groove. These are unique features among known species of Cambarellus.